Challenges and opportunities for carbon management in Malawi and Zambia. Issue 2 (April 2012) - Stringer, Lindsay C; Dougill, Andrew J; Mkwambisi, David D; Dyer, Jen C; Kalaba, Felix K; Mngoli, Mtisunge
Policy initiatives targeting carbon management are increasingly linking climate change mitigation and adaptation with efforts to reduce poverty and advance sustainable development. This article draws on empirical semi-structured interview data and documentary analyses to present an assessment of the challenges and opportunities faced by national policymakers and other key stakeholders in achieving these 'multiple wins'' in Malawi and Zambia. Lessons emerging from these study countries provide a useful basis for informing integrated carbon management, poverty reduction and sustainable development projects more widely in the southern Africa region. The findings reveal that multistakeholder partnerships are increasingly necessary, and we identify examples to illustrate that such collaborations are being established with varying degrees of success. The article suggests that discrete projects need to be adequately coordinated by umbrella organizations operating over larger scales in order to promote the longevity of project impacts at the local scale and to allow experiences and good practices to feed into national policy development. Capacity-building and resource investments across different levels are also shown to be vital.